Overview Of Emotional Regulation on Kindergarten Teachers In District: Gambaran Regulasi Emosi pada Guru Taman Kanak-Kanak di Kecamatan - Miftakhul Hepy Maharani; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to see the description of emotion regulation in kindergarten teachers in Sidoarjo sub-district. The data collection method in this study used descriptive quantitative methods. The variable of this research is emotion regulation. The population of this research is all 315 kindergarten teachers in Sidoarjo sub-district, with a sample of 200 teachers using random sampling technique. The data collection technique in this study used a Likert scale model. Analysis of the data in this study using SPSS 16.0 for windows. From the data analysis shows the value of r = 0,895 which means the emotional regulation scale is reliable. And in the category of emotional regulation, kindergarten teachers are in the medium category with a percentage value of (74%) indicating that kindergarten teachers in Sidoarjo sub-district are quite good. Highlights: The study focuses on describing emotion regulation in kindergarten teachers in Sidoarjo sub-district. Data collection method involves a sample of 200 teachers using random sampling technique. Analysis of data using SPSS 16.0 shows reliable emotional regulation scale and medium level of emotional regulation among kindergarten teachers in Sidoarjo sub-district (74%). Keywords: Emotion regulation, Kindergarten teachers, Sidoarjo sub-district, Descriptive quantitative methods, Likert scale model